O11: MYOFERLIN: A NOVEL BIOMARKER OF RADIOSENSITIVITY IN LOCALLY ADVANCED RECTAL CANCER. (27th April 2021) - Fowler, H; Sutton, P; Bowden, D; Parsons, J; Vimalachandran, D
Abstract: Introduction: Our proteomic data has validated that high levels of the protein myoferlin confers poorer response to neoadjuvant chemoradiotherapy in locally advanced rectal cancer. Myoferlin plays a role in membrane repair and VEGF signal transduction, and is associated with worse prognosis in numerous other epithelial cancers. We aim to assess the impact of myoferlin on the radiosensitivity of rectal cancer. Method: Clonogenic assays were performed using immortalised colorectal cancer cells (HCT116, HT29, LIM, MDST8) to assess survival at escalating radiation doses following knockdown with myoferlin siRNA or a small molecular inhibitor(WJ460). 3D models (spheroids) were used to examine the effect of WJ460 on tumour growth. Result: Quantification of myoferlin using immunoblotting demonstrated that MDST8 and LIM were higher expressors than HCT116 and HT29. Higher levels correlated with increasing radio‐resistance as calculated by colony formation efficiency (CFE). Using clonogenic assays, cells treated with myoferlin siRNA or WJ460 demonstrated increased radiosensitivity compared to controls across all radiation doses, most significantly at 4Gy. Treatment of spheroids with WJ460 significantly reduced growth compared to controls at all radiation doses (p<0.05), with WJ460 limiting growth considerably more than treatment with the current gold standard 5‐FU. HCT116 spheroid volume day 15; WJ460 4.96um 3, 5‐FU 6.74um 3, DMSO 24.9um 3 . Conclusion: Inhibition of myoferlin is associated with increased radiosensitivity of colorectal cancer cells, and treatment with a small molecular inhibitor significantly reduces growth in spheroid models. Further work is required further validate its potential use as a biomarker in locally advanced rectal cancer. Take‐home message: We have found that myoferlin is a protein associated with poor response to neoadjuvant chemoradiotherapy in locally advanced rectal cancer. Manipulation of this protein sensitises the cancer cells to radiotherapy.